Diets and nutrition: The potential of a food systems approach - Ruel, Marie T.; Brouwer, Inge D. (International Food Policy Research Institute, 2024)
As priorities in nutrition research and practice have evolved over time, food systems have increasingly become the organizing principle for work on nutrition and diets, with “food systems for sustainable healthy diets” emerging as the latest paradigm in nutrition. This chapter summarizes how learning from decades of work on the linkages between agriculture and nutrition paved the way to adopting the new food systems for sustainable healthy diets framework, and reflects on the emerging challenges and opportunities that arise for the nutrition community as we navigate this new global agenda.